Comparison via eher. (21st December 2021) - Umbach, Carla; Solt, Stephanie
Abstract: This paper is about the semantics of the German adverb eher, which has three, or perhaps four, readings: temporal, epistemic, metalinguistic and—depending on whether it is accepted as a genuine reading—preference. In its epistemic reading, eher gained prominence in semantics because it was used by Kratzer (1981) to argue that the notion of possibility is gradable. Eher has also received attention from a diachronic perspective, where it has been compared to the English adverb rather ( Gergel 2009 ). Our analysis starts from the temporal reading which, first of all, expresses temporal precedence. We argue that temporal eher is indexical (unlike früher /'earlier'), comparing closeness to a perspectival center, and that the non-temporal readings inherit their basic structure from the temporal one. The analysis of the non-temporal readings will be embedded in a Kratzer-style ordering semantics, deviating from the standard picture in assuming (i), that both the modal base and the ordering source are relativized to a perspective holder and (ii), that in the case of metalinguistic eher, interpretations (in the sense of Barker 2002 / Krifka 2012 ) are compared instead of worlds. Our analysis is different from that developed by Herburger & Rubinstein (2018), which ignores the temporal as well as the metalinguistic reading and takes recourse to "degrees of belief". At the end of the paper, we briefly look at expressions related to eher, including English more and its German counterpart mehr as well as English rather, and also at the modal reading of German schon ('already').